PENYULUHAN PENGELOLAAN SUMBER DAYA ALAM SECARA BERKELANJUTAN DI KAMPUNG PUTRA BULU DESA AWANG BANGKAL KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Bahrun; Hastirullah Fitrah (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Putra Bulu Village, Awang Bangkal Village is an area in Karang Intan District, Banjar Regency, South Kalimantan Province. This area is strategically located and close to popular natural tourist areas in Banjar Regency, such as the Meratus Geosite Geopark. The aim of extension is to provide knowledge to the community about sustainable management of natural resources, increase community awareness, knowledge and skills in managing the environment. Method of implementing community service using an approach method, namely providing knowledge to the community about sustainable management of natural resources, which is useful for increasing community awareness, knowledge and skills in managing the environment. The counseling is carried out in the form of lectures, discussions/questions and answers, with a total of 20 participants, the implementation time is approximately 2 hours. The implementer is the Community Service Team, Faculty of Agriculture, Achmad Yani University, Banjarmasin